A prayer for the dying [videorecording (DVD)] - Ward, Edmund, 1928-1993; Lynch, Martin; Garfath, Michael; Conti, Bill; Boyle, Peter, 1935-2006; Harrison, Evangeline; Rourke, Mickey; Hoskins, Bob; Bates, Alan, 1934-2003; Davis, Sammi; Fulford, Christopher; Neeson, Liam; et al. (Metro-Goldwyn-Mayer Studios, Inc., 2023)
As a school bus merrily speeds past an army caravan, it suddenly explodes. Stunned and horrified Martin Fallon (Mickey Rourke) flees. He had planted the bomb for soldiers, not to kill innocent children. Now, Fallon seeks to escape his violent life against all odds.